2022
DOI: 10.1002/lio2.877
|View full text |Cite
|
Sign up to set email alerts
|

Does human papillomavirus modify the risk of oropharyngeal cancer related to smoking and alcohol drinking? A systematic review and meta‐analysis

Abstract: Objective To synthesize evidence for interactions of traditional oropharyngeal squamous cell carcinoma (OPSCC) risk factors—tobacco smoking and alcohol drinking—with human papillomavirus (HPV). Data Sources MEDLINE, Embase, Cochrane Database of Systematic Reviews, ProQuest, and Global Health were searched with no restrictions on language or publication date. Methods All case–control studies assessing interactions between these factors in OPSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…First, we conducted a retrospective analysis of data from the SEER database, noting the absence of smoking and alcohol history, as well as molecular characterization. A systematic review and meta-analysis indicated a negative interaction between smoking and alcohol in the development of HPV (+) OPSCC [ 21 ]. In a previous study involving 157 OPSCC patients, gene alterations associated with oxidative stress were observed more frequently in HPV-positive cases, whereas those related to the p53 signaling and cell cycle control pathways were more prevalent in HPV-negative cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we conducted a retrospective analysis of data from the SEER database, noting the absence of smoking and alcohol history, as well as molecular characterization. A systematic review and meta-analysis indicated a negative interaction between smoking and alcohol in the development of HPV (+) OPSCC [ 21 ]. In a previous study involving 157 OPSCC patients, gene alterations associated with oxidative stress were observed more frequently in HPV-positive cases, whereas those related to the p53 signaling and cell cycle control pathways were more prevalent in HPV-negative cases [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the present retrospective study strongly focused at the level of (i) the EtG hair values and (ii) the oral occurrence of Streptococcus mitis , Candida albicans , Candida glabrata , and Neisseria subflava . In order to unveil the risk of alcohol consumption at the onset of UADT carcinoma, previous studies were mainly based on interviews that aimed to discover alcohol drinking habits without measuring the real, long-lasting alcohol consumption [ 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the above-mentioned factors are controllable: it is a matter of lifestyle choice in the case of the first two and being vaccinated in the case of the latter. It should be noted that the meta-analysis by Arif et al implied a negative synergy between HPV infection and smoking tobacco as well as HPV infection and high alcohol consumption, increasing the risk of primary OC development in a tiered and cumulative effect analysis [47]. Other risk indicators include Epstein-Barr virus (EBV, for nasopharyngeal carcinoma) [48,49], Candida albicans [50,51], a diet low in vitamin A and carotenoids, inadequate dental hygiene, including the regularity of tooth brushing, and chronic mouth trauma [52].…”
Section: Oral Cancer Risk Factorsmentioning
confidence: 99%